First record of the genus Cratolestes Hull, 1962 (Diptera: Asilidae: Asilinae) from Peru - Sánchez, Pável (2022)
Robber flies of the Neotropical genus Cratolestes Hull, 1962 are herein recorded for the first time from Peru. The two known species of this genus, Cratolestes chiliensis (Macquart, 1850) and Cratolestes wirthi Artigas, 1970, so far only recorded from Chile, are reported based on specimens deposited in the entomological collection of the Natural History Museum, Universidad Nacional Mayor de San Marcos, Lima, Peru (MUSM). A distribution map including the new Peruvian records is also presented